Bisnis Moda Berbasis Aplikasi Online bagi Kesejahteraan Ekonomi Driver Ojek Online di Jabodetabek - Sheila Wijayanti (Accounting Department UNUSIA, 2023)
The online application-based mode business in Indonesia is the impact of the digital era which is currently rampant. This business has a big influence on the economic welfare of online motorcycle taxi drivers, especially in the Jabodetabek area. The ease of accessing the online application offered can provide comfort to the public both in terms of use of public transportation, costs and promos obtained when the initial order is made. Thus, this business can affect the economic welfare of online motorcycle taxi drivers who become join the partners. The results of this study indicate that the mode of business based on online transportation applications has an effect on the economic welfare of online motorcycle taxi drivers, especially in the Jabodetabek area. This study aims to analyze the economic welfare of online motorcycle taxi drivers in the mode of business based on online transportation applications.